EFEKTIVITAS METODE SQUARE STEPPING EXERCISE DALAM MENINGKATKAN FUNGSI KOGNITIF PADA LANSIA DENGAN KONDISI DEMENSIA: CASE STUDY - Sari Triyulianti; Muawanah, Siti; Relida Samosir, Nova; Haikal Akbar, Muhammad (Universitas Muhammadiyah Metro, 2026)
Introduction: The aging process in older adults leads to various physiological changes, including a decline in nervous system function that may increase the risk of developing dementia. Dementia is a neurodegenerative syndrome characterized by decreased cognitive functions such as memory, orientation, attention, and thinking ability, which negatively affect independence and quality of life in older adults. This condition also increases the risk of mobility impairment and dependency in daily activities. Therefore, effective non-pharmacological interventions are needed to maintain and improve cognitive function. One such method is Square Stepping Exercise, a structured stepping-pattern-based physical exercise initially developed to improve balance in older adults, which has also been shown to stimulate cognitive function through enhanced concentration, memory, and motor coordination. This study aimed to determine the effectiveness of Square Stepping Exercise in improving cognitive function in older adults with dementia. Methods: This study employed a case study design involving one older adult with dementia and moderate cognitive impairment. The Square Stepping Exercise intervention was administered in 12 therapy sessions with a frequency of three times per week. Cognitive function was measured using the Mini Mental State Examination (MMSE) before and after the intervention. Results: After 12 sessions of Square Stepping Exercise intervention, an improvement in cognitive function was observed as measured by the Mini Mental State Examination (MMSE). The MMSE score increased from 13 (moderate cognitive impairment) before the intervention to 23 (mild cognitive impairment) after the intervention. Conclusion: Based on the results of this study, the implementation of Square Stepping Exercise for 12 therapy sessions demonstrated an improvement in cognitive function in older adults with dementia, as indicated by an increase in MMSE scores from the moderate cognitive impairment category to the mild cognitive impairment category. These findings suggest that Square Stepping Exercise has the potential to be used as a non-pharmacological intervention to improve cognitive function in older adults with dementia